Transgenerational transmission of childhood adversity: examining potential pathways to break the cycle of risk across generations - Fuchs, Anna (2017)
Child maltreatment is a widespread global phenomenon affecting the lives of millions of children all over the world. As these children grow up to be parents, they are at a higher risk of completing the so-called “cycle of abuse” and become perpetrators themselves. Only very recently, however, the spotlight has been moved from a limited focus on the intergenerational transmission of actual maltreatment on to further maladaptive outcomes in offspring of victims of child maltreatment. Hence, the number of studies investigating the subject is small, and core questions still remain unanswered. In addition, there is a lack of top-down theories enabling researchers to integrate evidence into a broader framework. Therefore, the aim of this work is to extend theoretical and empirical knowledge on transgenerational sequelae of maternal child abuse and neglect by 1) contributing an overarching model of transgenerational transmission of risk and 2) broaden the empirical data base by reporting results of four studies. Study 1 investigates the impact of a maternal history of childhood abuse (HoA) on mother-child interaction in a longitudinal case-control design. Results indicate that the period of developing child locomotion represents a critical time window for mothers with a HoA as they show less optimal mother-child interactional quality compared to a healthy control group during that phase. Study 2 examines mother-child interaction in mothers with depression in remission, mothers with a HoA, mothers with both depression in remission and a HoA, and comparison group mothers. Results reveal that depression affects maternal emotional availability even during remission. Furthermore, mothers with depression in remission and additional severe childhood abuse seem to be particularly affected. Study 3 investigates mother-child adrenocortical attunement in a community sample of mothers with a HoA and their five-months-old infants, matched with a healthy comparison group. Results confirm an association between maternal and infant salivary cortisol levels for the complete sample. However, in the comparison group, cortisol attunement was only significant in mother-daughter dyads, whereas in the maltreatment group, cortisol levels were associated only in mother–son dyads. Lastly, Study 4 examines whether children of the sample described in study 2 differ in inhibitory performance while taking into account their mothers reported impulsivity. There are no group differences in children’s inhibitory performance, however, maternal impulsivity moderates the association between group membership and child inhibition. Children whose mothers report a history of childhood abuse and high levels of impulsivity show lower levels of inhibition than children whose mothers report a HoA and low levels of impulsivity.